WORK ON PHRASEOLOGICAL UNITS IN PRIMARY GRADES - Sh. Yuldasheva; Ch. Primqulova (Zeta Repository, 2023)
The article describes phraseological units, expressions given in textbooks for elementary school, and the difficulties of their assimilation. For teachers, the methods and types of work used when working on phraseological units and developing students' speech are shown.